STUNTZ SM; THOMAS K - STUNTZ SM; THOMAS K (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Susan Stuntz and Kay Thomas to Samuel D. Chilcote Jr. regarding the stance of the American Federation of Government Employees (AFGE) on smoking restrictions in government buildings. Points out that up until new leadership took over, the union was divided, but with the new leadership it seems to be siding against smoking restrictions.